A systematic review of literature on hospitality internships. (June 2021) - Zopiatis, Anastasios; Papadopoulos, Constantinos; Theofanous, Yiannis
Abstract: Espousing experiential learning theories, internships have captured the attention of tertiary education programs in almost all business-related fields. Due to their vocational nature, hospitality and tourism programs have been amongst the first to incorporate such experiences in their curriculum, whereas relevant research has surged over the past two decades. This study aims to systematically review internship-specific literature, critique and synthesize the existing conceptual capital, identify important gaps, and highlight an agenda for future research. Sixty-nine articles are reviewed and analyzed with the use of a standardized coding scheme and content analysis. Findings, of interest to industry stakeholders, aim to enhance our understanding of the relevant literature and identify vital areas for future research that would further extend internship-related theories and practices. Finally, the impact of the unprecedented COVID-19 pandemic on internship practices is discussed, with suggestions aiming to highlight areas of both interest and concern.